Topological investigations of excess heat capacities of ternary mixtures containing chlorotoluenes and cyclic amides - A. ROHILLA; D. SHARMA; V. K. SHARMA (International Journal of Pharma and Bio Sciences, 2017)
Excess heat capacities, (CEP)123 1-methylpyrrolidin-2-one (1) + pyrrolidin-2-one (2) + o- or m- or p-chlorotoluene (3) ternary and CEP of 1-methylpyrrolidin-2-one (1) + pyrrolidin-2-one (2) binary mixtures have been determined at 293.15, 298.15, 303.15 K and 0.1 MPa using micro differential scanning calorimeter. The results were discussed in terms of Graph (which deals with the topology of the constituent molecules) and Flory’s theories. The results suggested that CEP and CEP values determined by Graph theory compared well with experimental values. Thermodynamics is the cornerstone for many scientific and engineering disciplines including physics, chemistry, chemical engineering, petroleum engineering and material science. It provides the basis for the design and optimization of new sustainable processes and the development of advance materials and products.